GIS-analysis of environmental quality of urban areas - Козлова, Т. В.; Шевченко, С. О. (Science-based technologies, 2011)
The results of using modern GIS technology for making to create digital cartographic models of areas’ atmosphere, acoustic and soil pollution in order to determine their environmental quality on the example of Khmelnitsky city are represented in this article. During the construction of thematic maps GIS-based system approach for mapping and analysis of pollution in urban areas is implemented.